Assessment Of Soil Boron Availability In Apple Orchards Using Different Extractants (Applied Biological Research, 2016)
Soil analysis for boron is vital as the range between its deficiency and toxicity is  quite narrow and its application slightly above the optimum level may prove  oxic to plants. In present study, the extractability of various extractants was  assessed in relation to the physicochemical properties of soils. Soil sampling  was carried out in 30 orchards in district Kulgam, Kashmir. Four extractants  widely used to determine plant-available boron from either acidic or alkaline  soils were used. The hot-water-soluble boron (HWSB) extraction procedure  was used as a benchmark to observe relative variation in available boron in  alternate extractants like calcium chloride-mannitol (CaCl2-mannitol),  ammonium acetate and diethylene-triaminepenta-acetic acid-sorbitol (DTPA sorbitol). A significant correlation was found for available B among all the  extractants tested, the strongest correlation (r = 0.975** at P
Keywords: Apple; ammonium acetate; CaCl2-mannitol; correlation; DTPA sorbitol; hot water; regression